Jean Gottmann as a Visionary and a Critic - Shuper, Vyacheslav A.; Kolosov, Vladimir A.; Fedorov, Gennady M. (International Journal of Economics and Financial Issues, 2015)
This is an introductory paper to the special issue on “The spatial transformation of the urban environment in the conditions of post-industrial development of society” conference dedicated to the 100th anniversary of Jean Gottmann. The conference was held at the Institute of Environmental Management, territory development and urban planning of the Immanuel Kant Baltic Federal University, Kaliningrad, Russia. The special issue presents a number of scientific papers, which represent different view angles on regional development in the context of globalization. Keywords: Jean Gottmann, Economic Geography, Regional Economy, Kaliningrad Region JEL Classifications: N9, O1, R1